2022
DOI: 10.1021/acsomega.2c01792
|View full text |Cite
|
Sign up to set email alerts
|

Using Amphiphilic Polymer Micelles as the Templates of Antisolvent Crystallization to Produce Drug Nanocrystals

Abstract: Biocompatible and biodegradable amphiphilic polymeric micelles (PLA-CMCS-g-OA) were prepared by surface grafting of oleic acid and polylactic acid onto carboxymethyl chitosan and were used as templates for the crystallization of camptothecin. The camptothecin (CPT) nanocrystals prepared by the novel micelle-templated antisolvent crystallization (mt-ASC) method demonstrated higher crystallinity, narrower particle size distribution, and slower release characteristic than those prepared by conventional antisolven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…After the reaction, analysis through 1 H-NMR of the reaction material was conducted, and results showed that the AA-CMCS conjugate was successfully prepared [ 26 ]. Amide bond formation between the carboxyl group of AA and the amine bond of CMCS was responsible for the formation of AA-CMCS conjugate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the reaction, analysis through 1 H-NMR of the reaction material was conducted, and results showed that the AA-CMCS conjugate was successfully prepared [ 26 ]. Amide bond formation between the carboxyl group of AA and the amine bond of CMCS was responsible for the formation of AA-CMCS conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of a characteristic ring of methine protons of AA-CMCS conjugate spectra in the region of 5.55–5.44 ppm proved the grafting of CMCS with AA in the AA-CMCS conjugate as shown in Figure S3 . Also, the broadening of peaks of (CH 2 )n and conjugated double bonds were observed at 1.7 ppm and 5.5 ppm in the spectra of the AA-CMS conjugate which was due to the presence overlap of the methylene proton adjacent to a double bond with the acetamide group protons [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In antisolvent crystallization, the antisolvent or precipitant provides the driving force of the supersaturation of the solute (drug) by decreasing its solubility [28][29][30][31][32][33][34]. Antisolvent crystallization has numerous advantages compared to the other crystallization methods, such as low cost, ease of scale-up, and superior control on the polymorph and size distribution of drug crystals, which can consequently lead to the enhancement of the final API solubility.…”
Section: Figure 1 (A) Schematic Illustrationmentioning
confidence: 99%